Validity of the Hartmann operation in the treatment of complicated colonic diverticulosis: study carried out in patients treated during the period 2009-2018, at Hospital de Clínicas, Montevideo - Barberousse, Carlos; Ramírez, Luciano; Dardanelli, Santiago; Fernández, Lucía (Cirugía del Uruguay, 2021)
Introduction and objectives: Complicated diverticular disease is a health problem that affects elderly patients and often requires surgical treatment. Options are multiple, being Hartmann procedure an old and still valid alternative. The objective of the present study was to evaluate the validity of this procedure in our environment through an analytical study of a population in a University Hospital of Montevideo. Materials and methods: Analyze the medical records of patients older than 20 years operated on in the period 2009-2018. Consider the following variables: surgical procedures, peri-operative complications, re-treatments, rate and time of reconstruction of the digestive transit and mortality. Results: 27 patients were operated in the analyzed period, with a mean age of 59.4 years. In 15 of them, a Hartmann procedure was performed. In the remaining patients, procedures performed were approach both ends, primary anastomosis with or without a proximal stoma, and assisted video washing and drainage without resection. Eleven patients (40%) presented peri-operative complications. Peri-operative mortality was four patients (14.8%), all corresponding to Hartmann's operation. The recovery rate was six of 11 surviving patients. Discussion: The Hartmann operation maintains the validity and the most used procedure, being its considerable morbidity and mortality and the recovery rate of approximately half of the patients. The primary anastomosis should be reserved for selected cases. The development of laparoscopic surgery has also allowed conservative procedures, such as washing and drainage, avoiding acute resection, this option being a growing trend. Conclusions: It was concluded that the series, although short, reproduce what was reviewed in the bibliography.